Phosphorylation of cardiac myosin–binding protein-C contributes to calcium homeostasis - Kumar, Mohit (J Biol Chem, 2020)
Cardiac myosin–binding protein-C (cMyBP-C) is highly phosphorylated under basal conditions. However, its phosphorylation level is decreased in individuals with heart failure. The necessity of cMyBP-C phosphorylation for proper contractile function is well-established, but the physiological and pathological consequences of decreased cMyBP-C phosphorylation in the heart are not clear. Herein, using intact adult cardiomyocytes from mouse models expressing phospho-ablated (AAA) and phosphomimetic (DDD) cMyBP-C as well as controls, we found that cMyBP-C dephosphorylation is sufficient to reduce contractile parameters and calcium kinetics associated with prolonged decay time of the calcium transient and increased diastolic calcium levels. Isoproterenol stimulation reversed the depressive contractile and Ca(2+)-kinetic parameters. Moreover, caffeine-induced calcium release yielded no difference between AAA/DDD and controls in calcium content of the sarcoplasmic reticulum. On the other hand, sodium–calcium exchanger function and phosphorylation levels of calcium-handling proteins were significantly decreased in AAA hearts compared with controls. Stress conditions caused increases in both spontaneous aftercontractions in AAA cardiomyocytes and the incidence of arrhythmias in vivo compared with the controls. Treatment with omecamtiv mecarbil, a positive cardiac inotropic drug, rescued the contractile deficit in AAA cardiomyocytes, but not the calcium-handling abnormalities. These findings indicate a cascade effect whereby cMyBP-C dephosphorylation causes contractile defects, which then lead to calcium-cycling abnormalities, resulting in aftercontractions and increased incidence of cardiac arrhythmias under stress conditions. We conclude that improvement of contractile deficits alone without improving calcium handling may be insufficient for effective management of heart failure.